Geographic Differentiation of Colombian Neoleucinodes elegantalis (Lepidoptera: Crambidae) Haplotypes: evidence for solanaceae host plant association and Holdridge life zones for genetic differentiation - Díaz Montilla, Ana Elizabeth; Suárez Baron, Harold; Gallego-Sanchez, Gerardo; Saldamando Benjumea, C.I.; Tohme, Joseph M. (Oxford University Press, 2013)
The purpose of this study was to examine the population structure of Neoleucinodes elegantalis (Guenée) (Lepidoptera: Crambidae) in relation to host plant association and ecological Holdridge zones. Adult collections were made in cultivated and wild Solanaceae species in 13 departments of Colombia. Sequencing of 658 bp of the mitochondrial gene Cytochrome Oxidase 1 on 103 individuals produced 25 haplotypes. Haplotypes Hl, H2, H4, and H7 were the most frequent and were geographically separated by the Andean mountains. We obtained an FST = 0.57 (P < 0.0001), where most of the genetic differentiation (42.64%) was between individuals within each department. Pairwise FST analysis produced higher genetic values between geographically separated departments than between closely related sites. H2 and H7 apparently behave as generalist populations, as they were found in different habitats and different hosts. The most divergent populations of N. elegantalis were found in southern Colombia, at a location were Solanun quitoense might have originated. Host plant association and environmental factors such as Holdridge life zones are playing an important role in the differentiation of N.elegantalis. Population structuring in N.elegantalis indicates that integrated pest management strategies used to control this species should consider the genetic differentiation of the species at different locations in Colombia.